Postrape care services to minors in Kenya: are the services healing or hurting survivors? - Wangamati CK; Combs Thorsen V; Gele AA; Sundby J (Dove Medical Press, 2016)
Cynthia Khamala Wangamati,1 Viva Combs Thorsen,1 Abdi Ali Gele,2 Johanne Sundby1 1Department of Community Medicine, Faculty of Medicine, University of Oslo, 2Department of Nursing and Health Promotion, Faculty of Health Sciences, Oslo and Akershus University College of Applied Sciences, Oslo, Norway Abstract: Child sexual abuse is a global problem and a growing concern in Sub-Saharan Africa. It constitutes a profound violation of human rights. To address this problem, Kenya has established the Sexual Offences Act. In addition, Kenya has developed national guidelines on the management of sexual violence to grant minors access to health care. However, little is known about the experiences of sexually abused minors when they interact with the health and legal system. Accordingly, this study uses a triangulation of methods in the follow-up of two adolescent girls. Health records were reviewed, interactions between the girls and service providers were observed, in-depth interviews were conducted with the girls, and informal discussions were held with guardians and service providers. Findings indicated that the minors’ rights to quality health care and protection were being violated. Protocols on postrape care delivery were unavailable. Furthermore, the health facility was ill equipped and poorly stocked. Health providers showed little regard for informed assent, confidentiality, and privacy while offering postrape care. Similarly, in the justice system, processing was met with delays and unresponsive law enforcement. Health providers and police officers are in grave need of training in sexual and gender-based violence, its consequences, comprehensive postrape care, and sexual and reproductive health rights to ensure the protection of minors’ rights. Health administrators should ensure that facilities are equipped with skilled health providers, medical supplies, and equipment. Additionally, policies on the protection and care of sexually abused minors in Kenya require amendment. Keywords: child sexual abuse, postrape care, rights, guidelines, sexual violence